Transformasi Digital Governance Dalam Pelayanan Publik Dan Tantangan Implementasi - Hafiz Randika Putra; Theo Marchelindo; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Digital governance transformation has become one of the primary agendas of public sector reform worldwide, including in Indonesia. The rapid advancement of information and communication technology has encouraged governments to shift from conventional governance systems toward more effective, efficient, transparent, and accountable digital governance. This article aims to analyze the role of digital governance transformation in improving public service quality and to identify challenges in its implementation. This study employs a literature review approach by examining academic articles, books, and policy documents published between 2020 and 2025. The findings indicate that digital governance contributes significantly to service efficiency, government transparency, public accountability, citizen participation, and data-driven decision making. However, its implementation continues to face various challenges, including limited digital infrastructure, inadequate human resource competencies, regional digital disparities, bureaucratic resistance to change, and issues related to data security and privacy. The success of digital governance transformation is strongly influenced by leadership quality, regulatory support, organizational readiness, and public participation. This study contributes by providing a comprehensive literature synthesis that can serve as a foundation for future policy development and research on digital government transformation.